Cost analysis of inpatient hypertension patients at Panembahan Senopati Hospital, Bantul, Yogyakarta, Indonesia: comparison between INA-CBGs rates and hospitalized actual rate: 10.55131/jphd/2023/210312 - Nilansari, Anis Febri; Nanang Munif Yasin; Diah Ayu Puspandari (Journal of Public Health and Development, 2023)
Hypertension as a cardiovascular disease ranks first as a disease with the highest expenditure on health insurance costs. In the financing system implemented by the Indonesian Social Security Program, hospitals as health service providers no longer break down bills based on details of services provided, but only by submitting a diagnosis code that comes out in the form of Indonesia Case-Based Groups (INA-CBGs). The INA-CBGs code for mild hypertension with a severity level of 1 is I-4-17-1. The purpose of this study was to determine the implementation of INA-CBGs rates by comparing the cost difference between the INA-CBG rates and the actual hospital rates for inpatients with hypertension code I-4-17-1 with the parameters studied in the form of gender, age, and length of stay, comorbidities, and drug usage. The analytic observational method with a cross-sectional design was used. Data were hospital financial records and patients medical record documents (inpatient hypertension patients) coded I-4-17-I with the following classes; first class, second class, and third class treatment rooms from October 2016 to July 2017 at Panembahan Senopati Hospital. Data were tested for normality with the Kolmogorov-Smirnov test. One Way ANOVA test and t-test were used to analyze the data in determining the difference in costs between the INA-CBGs rates and the actual hospital rates and in determining the factors that influenced the difference in costs. The results showed that 53 patients met the inclusion criteria. The total cost incurred by the hospital for hospitalized hypertensive patients was Rp. 140,963,105, while the total claim rate for INA-CBGs was Rp. 109,960,000. Gender, length of stay, comorbidities, and drug usage were contributed to the difference in cost, while age had no significant effect. It can be concluded that hospitals need to evaluate the implementation of INA-CBGs rates to minimize financial losses.